ANALISIS PANDANGAN ANAK MUDA DI SURABAYA TIMUR DALAM PERBANDINGAN KEBAYA ENCIM DAN KEBAYA JAWA - Morse, Audrey; Leonardo, Ong Peter (Universitas Widya Kartika Surabaya, 2024)
Kebaya is a traditional Indonesian clothing that is popular among women and has been known for a long time by many people in various countries, because it can display elegance when worn, besides that kebaya clothing is also an Indonesian cultural heritage. One of the kebaya known to the public is the Javanese kebaya, then the entry of Chinese culture emerged kebaya encim. This study was conducted to analyze the views of young people in East Surabaya in the comparison of Kebaya Encim and Kebaya Jawa. The comparison was made based on the similarities and differences in Kebaya Encim and Kebaya Javanese according to the views of young people in East Surabaya with questionnaire research methods and interviews, sampling from young people in the East Surabaya area.Based on this research, it can be seen that the views of young people in East Surabaya in comparison are bright colors and the average motif is related to flowers or other motifs that contain elements of Chinese culture and Javanese Kebaya which is worn with kemben and is identical to brocade.